ISSR markers and population differentiations in Erodium ciconium (L.) L'hér ex Aiton (Bangladesh Journal of Plant Taxonomy, 2021)
Erodium ciconium is an important grazing plant and a source of protein supplements to straw for ruminants in semideserts and wastelands of the Middle East. There is no information on its population genetic structure, genetic diversity, and morphological variability in Iran. We performed molecular data for knowing the population differentiation in this species. For this study, we used 110 randomly collected plants from 15 geographical populations in 6 provinces of Iran. AMOVA test revealed significant genetic difference among the studied populations and also revealed that, 63% of total genetic variability was due to within population diversity while, 37% was due to among population genetic differentiation. Mantel test showed positive significant correlation between genetic distance and geographical distance of the studied populations. Networking, STRUCTURE analyses revealed some degree of gene flow among these populations.Bangladesh J. Plant Taxon. 28(1): 61-73, 2021 (June)